2022
DOI: 10.1186/s12889-022-14527-5
|View full text |Cite
|
Sign up to set email alerts
|

Mental health challenges and perceived risks among female sex workers in Nairobi, Kenya

Abstract: Background Female sex workers (FSWs) in Kenya are at an increased risk of violence, poverty, police arrest, and problematic alcohol and other substance use, all of which are linked to poor mental health and suicidal ideation. Despite the psychological stressors experienced by FSWs, there is no published qualitative methods research investigating their mental health experiences in Kenya. In this paper, we draw on data from in-depth interviews to examine FSWs’ lifetime mental health experiences a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
1
0
4
Order By: Relevance
“…This finding suggests that specific subpopulations within KPs may have distinct mental health needs and risk factors. Similar studies have demonstrated the unique challenges FSW and PWID face regarding mental health [23,24]. Tailoring mental health support to these subgroups is imperative.…”
Section: Plos Onementioning
confidence: 76%
“…This finding suggests that specific subpopulations within KPs may have distinct mental health needs and risk factors. Similar studies have demonstrated the unique challenges FSW and PWID face regarding mental health [23,24]. Tailoring mental health support to these subgroups is imperative.…”
Section: Plos Onementioning
confidence: 76%
“…Três estudos abordaram a ligação entre fatores socioeconômicos e a ideação suicida 9,13,25 tendo em vista que muitas mulheres demonstraram apreensão por não conseguirem manter a si e a seus dependentes, e relacionaram isso ao desejo de finalizar a própria vida. A exemplo disso, há um relato obtido através de uma pesquisa longitudinal no Quênia, na qual uma profissional do sexo afirmou: "Pensei em comprar veneno; Eu mato a mim e a todos os meus filhos também, com isso a vida acabaria.…”
Section: Ciência Pluralunclassified
“…A exemplo disso, há um relato obtido através de uma pesquisa longitudinal no Quênia, na qual uma profissional do sexo afirmou: "Pensei em comprar veneno; Eu mato a mim e a todos os meus filhos também, com isso a vida acabaria. Agora eu não tenho dinheiro (para comprar veneno) [...], vou perguntar quanto custa o veneno de rato, dou a todos os meus filhos e bebo também e todos morremos à noite (MF 497)" 25 .…”
Section: Ciência Pluralunclassified
See 2 more Smart Citations